2020
DOI: 10.1002/nop2.447
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health‐promoting behaviours, eating behaviour patterns and perceived social support in normal‐weight and overweight pregnant women: An unmatched case–control study

Abstract: Aim The interventions based on adopting a healthy lifestyle during pregnancy have conflicting results. This study aimed to compare health‐promoting, dietary patterns and social support in normal and overweight pregnant women. Design An unmatched case–control design was used. Methods A total of 360 pregnant women were selected using multistage cluster sampling and divided into two groups of normal and overweight cases. Data were collected using demographic and obstetrics characteristics, health‐promoting lifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 39 publications
(44 reference statements)
4
2
2
Order By: Relevance
“…The results showed involved women had a higher body mass index than the control group, which could represent inappropriate nutrition. The results also in line with the results of our previous study on pregnant women [ 7 , 51 ]. While the majority of pregnant mothers want to change their behavior and ability to provide healthy food and physical activity, many women believe such changes are outside their control [ 20 ], according to other researchers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results showed involved women had a higher body mass index than the control group, which could represent inappropriate nutrition. The results also in line with the results of our previous study on pregnant women [ 7 , 51 ]. While the majority of pregnant mothers want to change their behavior and ability to provide healthy food and physical activity, many women believe such changes are outside their control [ 20 ], according to other researchers.…”
Section: Discussionsupporting
confidence: 92%
“…This difference can be attributed to the cultural differences and gestational age of study participants, because they studied pregnant women in their second trimester, which women have more stable condition than their third trimester. The difference between scores of two groups were important and the results are comparable with other studies in such a way that in some studies, obese women and overweight women as high-risk pregnancies had lower scores compared to the comparison groups [ 7 , 45 ]. Studies on women with preeclampsia also indicate that health promoting life style behaviors is not so suit in these women [ 2 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Physical activity had the lowest score which is in line with the other studies conducted in Iran [18,21],…”
Section: Discussionsupporting
confidence: 91%
“…The current ndings showed that the total score of HPLP-II among the pregnant women of Siyari Municipality was at a moderate level, which is less than the ndings of earlier studies from Iran [18, [21][22][23], and from Turkey [24]. The variations might be due to the differences in cultural norms, values, and lifestyle habits of the participants.…”
Section: Discussioncontrasting
confidence: 88%